In vitro digestion and human gut microbiota fermentation of Bletilla striata polysaccharides and oligosaccharides - Wang, Qiqi; Chen, Huimin; Yin, Mingzhu; Cheng, Xue; Xia, Hui; Hu, Haiming; Zheng, Junping; Zhang, Zhigang; Liu, Hongtao (Frontiers in Cellular and Infection Microbiology, 2023)
Background Bletilla striata is one of the commonly used traditional Chinese medicine. B. striata polysaccharides (BP) and oligosaccharides (BO) are one of the main components of B. striata, which have been proved to have a variety of biological activities. However, the digestion and fermentation characteristics of BP and BO are still unclear. Methods The study evaluated different prebiotic effects of BP and BO by in vitro simulating digestion and gut microbiota fermentation. Results The results show that the simulating saliva partly degraded BP, but had no effect on BO. The molecular weights of BP and BO remained basically unchanged in gastric and intestinal digestion. In addition, BP and BO could be rapidly degraded and utilized by gut microbiota. During in vitro fermentation, the growth rates of the BP and BO groups were higher than that of the Control group and the pH value and total carbohydrate content in BP group and BO group decreased significantly. Although the reducing sugar level in the BO group decreased rapidly, it remained at a low level in the BP group. Both BP and BO improved the composition and structure of gut microbiota, indicative of the upregulated abundances of Streptococcus and Veillonella, and the downregulated populations of Escherichia and Bacteroides. There were differences in the SCFA production by gut microbiota and antioxidant activities between the BP and BO groups. The fermentation broth of the BP group displayed a stronger suppression of O2-, but a higher scavenging effect on DPPH for the BO group. Conclusions BP and BO displayed different digestion and fermentation characteristics in vitro due to their distinct polymerization degrees. The study point towards the potential of BP and BO as prebiotics in the application to human diseases by selectively regulating gut microbiota in the future.